Health Profile of Precarious Migrants Attending the Médecins Du Monde's Health and Social Care Centres in France: a Cross-Sectional Study - Emeraude Halley; Joris Giai; Marielle Chappuis; Anne Tomasino; Roland Henaine; Roland Henaine; Laurent Letrilliart; Laurent Letrilliart (Frontiers Media S.A., 2021)
Objective: The present study aimed to compare the precarious migrants' health problems managed in Médecins du Monde's health and social care centres (CASO) with those of patients attending general practice in France.Methods: We compared the most frequent health problems managed in the 19 CASO in metropolitan France with those of a national sample of usual general practice consultations, after standardisation for age and sex.Results: Precarious migrants had fewer health problems managed per consultation than other patients (mean: 1.31 vs. 2.16), and these corresponded less frequently to chronic conditions (21.3% vs. 46.8%). The overrepresented health problems among CASO consultations were mainly headache (1.11% vs. 0.45%), viral hepatitis (1.05% vs. 0.20%), type 1 diabetes (1.01% vs. 0.50%) and teeth/gum disease (1.01% vs. 0.23%). Their underrepresented health problems were mainly lipid disorder (0.39% vs. 8.20%), depressive disorder (1.36% vs. 5.28%) and hypothyroidism (0.50% vs. 3.08%). Prevention issues were nominal in precarious migrants (0.16%).Conclusion: Both chronic somatic and mental conditions of precarious migrants are presumably underdiagnosed. Their screening should be improved in primary care.